Which Gradualism? Whose Relationships?. Issue 1 (13th May 2016) - King, Jason
Abstract : The 2014 extraordinary meeting of the Synod of Bishops explicitly referenced gradualism three times in the Relatio post Disceptationem . Is this moral theology concept helpful for analyzing relationships? This question is more difficult than it first seems. One needs to first ask "which gradualism, " as the three references imply three different understandings: Gradualism as Growth in Holiness, Gradualism as Pastoral Practice, and Gradualism as Inclusivism. Second, one must ask "whose relationship" it can help. I turn to hookup culture as it is a ubiquitous phenomenon on college campuses. As only Gradualism as Inclusivism proves helpful in hookup culture, it has the best potential to help those pursuing good relationships that might not readily align with church teaching.